Researching writing : an introduction to research methods - Kinkead, Joyce A., 1954- (2016)
"An accessible, informative textbook that teaches undergraduates how to conduct ethical, authentic research in writing studies. The book introduces students to the research approaches used most often, and offers a course framework for professors creating or teaching research courses themselves"--Provided by publisher.
Includes bibliographical references.
Keywords: English language -- Rhetoric -- Textbooks